Exploring biomimicry in agriculture focuses on how insights from natural systems can revolutionize farming practices and enhance food security - Othmani Nurul Izzati; Wan Mohamad Wan Saiful Nizam; Abdul Hamid Nor Hamizah; Ramlee Noorliyana; Yeo Lee Bak; Hasan Ramly; Ibrahim Ismi Luqman Hamadi; Mustapa Nor Diyana; Mohd Jain Noordin Mohd Azri; Khairuddin Muhammad Rizal; Othmani Iylia Athirah (BIO Web of Conferences)
Biomimicry, a design philosophy that is based on the principles of nature, presents a promising solution to the sustainability challenges faced by modern agriculture. Biomimicry agriculture endeavours to replicate the efficacy, resilience, and sustainability of natural systems by drawing inspiration from ecosystems. By analysing agricultural challenges and identifying the biomimicry approach in previous research, this study investigates the alternative method in biomimicry to ensure a sufficient food supply for agriculture. This document examines the adoption of biomimicry in the agricultural sector. A comprehensive content analysis of four case studies that concentrated on biomimicry farming systems and their integration with agricultural design was conducted. The case study selection was determined by the concept of biomimicry, which involves the transfer of inspiration from nature to the commonplace built environment. The results indicate that the design of Biomimicry is anticipated to enhance the efficacy of agriculture and technology in terms of environmental sustainability and well-being. The urban environment can be transformed through the application of biomimicry, as evidenced by this agricultural study. In summary, biomimicry has the potential to significantly improve the sustainability and resilience of agriculture. It has the potential to create innovative solutions that improve food security, conserve natural resources, and reduce the environmental effects of cultivation.